Resistance of Heterogeneous Metal Compositions to Fracture under Dynamic and Cyclic Loads; Metals; Vol. 13, iss. 11 - Leshchinsky L. K. Leonid Konstantinovich; Ivanov V. P. Vitaly Petrovich; Lavrova E. V. Elena Vladimirovna; Ilyashchenko D. P. Dmitry Pavlovich (2023, 2023)
Title screen